Observation of Frenkel and charge transfer excitons in pentacene single crystals using spectroscopic generalized ellipsometry - Qi, Dongchen (2013)
We report on the emerging and admixture of Frenkel and charge transfer (CT) excitons near the absorption onset in pentacene single crystals. Using high energy-resolution spectroscopic generalized ellipsometry with in-plane polarization dependence, the excitonic nature of three lowest lying excitations is discussed. Their distinct polarization dependence strongly indicates the presence of both Frenkel and CT types of excitons near the excitation onset. In particular, the peculiar polarization behavior of the second excitation can only be rationalized by taking into account the inherent CT transition dipole moment. This observation has important implications for the pentacene-based optoelectronic devices.